Surrounding the reason for women to continue the tradition of child marriage - NURMALA, I; ASTUTIK, F.N; DEVI, Y.P (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Both the words “child” and “marriage” are sometimes interpreted differently. Child marriage brings health problems especially to women who currently remain experiencing gender inequality. This unpreparedness to get married can contribute to maternal and infant mortality. Using a qualitative design with an in-depth interview, this study explores the underlying reasons for women to continue the child marriage tradition in Sumenep Indonesia. The primary health center has conducted several interventions in the form of education and socialization. Religious Affairs Office in Indonesia needs to create a program to improve knowledge and understanding of the risk in continuing child marriage tradition.